Development of Hospital Environmental Management Model through PAIC Process - Jongwutiwes, Nipaporn; Thiengkamol, Nongnapas; Thiengkamol, Tanarat (Mediterranean Journal of Social Sciences, 2012)
The most importance of hospital environmental management must be pay attention on worker behavior in theireveryday practicing at hospital. Therefore, the most rapid and cheapest mean is to challenge the worker to collaborate energyeffectively utilization, waste management, wastewater management and landscape architectural environment via the humanresource strengthening with the worker based on the concept positive thinking like as owner. Environmental education concept ispertinent to sustainable principles that covers knowledge and understanding, awareness, attitudes, values, and belief,responsibility, participation, and skill necessary to build a sustainable hospital management. The objective of this research wasto develop hospital environmental management in Roi-Et Province through PAIC Process. The integrative research will be donewith quantitative in terms of survey research and participatory action research with Participatory Appreciate-Influence-Controltechnique (PAIC) ) and qualitative focus group discussion. Populations are all hospital workers. The sample was selectedaccording to purposive sampling technique. The PAIC was implemented with hospital workers integrating with SWOT Analysisand brain storming in the process. During training, Three Dimensional Evaluation (TDE) covers self-evaluation, friendevaluation,and facilitator evaluation. One -Way-ANOVA, and t-test were used for data analysis. The research results illustratedthat before and after PAIC process implemented, the mean scores of posttest of knowledge of environmental educationprinciples, energy conservation, waste water management, solid and infectious waste management, green landscape andtraining achievement were higher than pretest with statistical significance (p< .01, p< .01, p< .01, p< .01, p< .01, and p< .01 ).Three Dimensional Evaluations were employed for determination the perceptions of 32 hospital workers in three aspectsevaluation covering Self-evaluation, Friend-evaluation, and Facilitator-evaluation by using One-way ANOVA in order toinvestigate the participation of hospital workers showed that there were no difference of mean scores about participation intraining process through brain storming with statistical significance (p>.05).